2011
DOI: 10.4166/kjg.2011.57.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acid Pump Antagonist (Revaprazan, Revanex®) on Result of13C Urea Breath Test in Patients withHelicobacter pyloriAssociated Peptic Ulcer Disease

Abstract: False negative results of UBT were common and increased with prolonged use of acid pump antagonist. As PPI, it had also anti-urease activity and most patients (47/52, 90.4%) reverted to positive results by 2 weeks after the cessation of taking the medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…H. pylori detection in our study was based on histological and immunostaining methods. Other studies utilizing UBT as the main method of detecting H. pylori revealed false UBT-negative results in around one-third of patients [4,5,17,18] . Dickey et al [19] concluded in their study that PPI use before endoscopy was associated with lower sensitivity of antral and corpus biopsies for the detection of H. pylori using both urease testing and histological examination.…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori detection in our study was based on histological and immunostaining methods. Other studies utilizing UBT as the main method of detecting H. pylori revealed false UBT-negative results in around one-third of patients [4,5,17,18] . Dickey et al [19] concluded in their study that PPI use before endoscopy was associated with lower sensitivity of antral and corpus biopsies for the detection of H. pylori using both urease testing and histological examination.…”
Section: Discussionmentioning
confidence: 99%
“…It can be used before therapy and to confirm eradication . One of the limitations of the UBT is the possibility of false negative results in the following conditions: 1, use of proton‐pump inhibitors (PPI), antibiotics, or bismuth 2 weeks before the test ; 2, UBT carried out <4 weeks after finishing a course of eradication ; and 3, gastric resection . So even if UBT is an excellent test when performed correctly in research protocols, we wanted to see how it performs in clinical practice and whether its accuracy could be affected by protocol violations.…”
mentioning
confidence: 99%